Lung angiotensin converting enzyme activity in rats with pulmonary hypertension. Issue 3 (March 1982) - Keane, P M; Kay, J M; Suyama, K L; Gauthier, D; Andrew, K
Abstract : We have studied serum and lung tissue angiotensin converting enzyme (ACE) activity in female Wistar rats with pulmonary hypertension induced by two different methods. Chronic pulmonary hypertension was produced in one group of 10 rats (CH) by confinement in a hypobaric chamber (380 mmHg) for three weeks, and in another group fo 10 rats (M) by a single subcutaneous injection of monocrotaline (60 mg/kg body weight). In these two groups of tests rats and in 20 untreated controls (C), we evaluated right ventricular mean systolic blood pressure (Prvs mmHg), right ventricular hypertrophy, and serum ACE (n mol/ml/min). In lung tissue homogenate, we measured the specific activity of ACE (n mol/mg protein/min), alkaline phosphatase (AP) (IU/mg protein) and lactic dehydrogenase (LDH) (IU/mg protein). The Prvs in groups, C, CH, and M was 25 +/- 7 SD, 41 +/- 7, and 51 +/- 5, respectively. The ratio of right ot left ventricular weight (RV/(LV + S)%) in groups, C, CH, and M was 29 +/- 4, 52 +/- 5, and 56 +/- 7, respectively. The lung tissue ACE in groups C, CH, and M was 85 +/- 11, 65 +/- 20, and 22 +/- 5, respectively. In groups CH, and M the Prvs and RV/(LV + S)% were significantly elevated above control values while lung ACE was significant decreased (p less than 0.05). There was a significant inverse relationship between lung ACE on one hand, and Prvs (r = - 0.73) and RV/(LV + S)% (r = - 0.71) on the other hand. Serum ACE and lung AP were unchanged. In group M there was a slight but significant reduction in lung LDH. Chronic pulmonary hypertension, irrespective of its method of production, is associated with decreased lung ACE. The reduction in lung ACE is inversely proportional to the severity of pulmonary hypertension and right ventricular hypertrophy.